Minat Belajar Mahasiswa Pada Mata Kuliah Ekologi Hewan Selama Masa Pandemi Covid-19 - Ruth Megawati (Arden Jaya Publisher, 2021)
The type of this research is a quantitative descriptive, with the population is all students who program animal ecology courses. The sampling technique is the saturated sampling technique, which takes all of the population as research samples, as many as 36 people. The research instrument is a closed questionnaire about interest in learning. This questionnaire was made using a Likert scale with alternative answer choices Strongly Agree (SS) with a score of 4, Agree (S) with a score of 3, Disagree (TS) with a score of 2, Strongly Disagree (STS) with a score of 1. Data collection techniques are carried out by both (1). Online questionnaires via google form; and (2). Took interviews with several students to confirm the answers based on the questionnaire. The technique of data analysis is the percentage formula, then confirmed in the table of criteria for scores acquisition of interest in learning outcomes. The results of this research on each indicator of interest show that there are differences in each obtained of the results. The indicator of feeling happy to attend lectures on animal ecology courses are in the medium category with a percentage of 58%, then the indicator of attention to lectures is in the less category with a percentage of 40%, the indicator of willingness to always active in attending the course is also in the less category with a percentage of 37%, and the indicator of interest in animal ecology course is in the medium category with a percentage of 60%. Overall, based on all indicators, students' interest in studying animal ecology course is in the moderate category with a percentage of 48, 75%.